PENGUKURAN PEMILIHAN SAHAM DAN PENETAPAN WAKTU MENGGUNAKAN MODEL TREYNOR-MAZUY PADA REKSADANA SYARIAH DI INDONESIA - Anita Anita (ETIKONOMI, 2013)
This research aims is to evaluate performance of sharia mutual fund in Indonesia by assessing investment manager’s ability and by inserting public information for considering investment in capital market. This research uses Treynor-Mazuy’s model  that is in turn developed by Ferson-Walther’s model  for conditional version. The statistic method to test on this study are Multiple Regression and Autoregressive Conditional Heteroscedasticity (ARCH). Based on examination result of two sharia equity mutual fund data shows that stock selection ability of investment manager give a positive contribution to the fund returns, while market timing ability give a negative contribution to fund returns. , and public information that is relied on in making decision for investment of Sharia capital market is information about changes of exchange rate.DOI: 10.15408/etk.v12i1.1898